ADVANCING STUDENTS’ SPEAKING SKILL WITH SERIES OF PICTURES - Gesang Permana, Rian Sigit (LinguaScopes: International Journal of Language Education, 2024)
This study was aimed at describing the implementation of a series of picture activities and describing whether or not a series of picture activities improves the student’s speaking skills. This research consisted of one cycle with each cycle consisting of four elements; they are planning, acting, observing, and analysis and reflection. This study was implemented in MTS Ma’arif Keputran in the Second grade, using classroom action research. The writer took 39 students as the subject of the research. In this research, the classroom action research (CAR) was done by the writer and the English teacher. The writer worked together collaboratively with the English teacher; the English teacher of MTS Ma’arif Keputran taught English and the writer who took part in this research as a collaborator to assist in the implementation of a series of picture activities and to observe the outcomes. In this research, the writer collects the data using observation sheets to observe the students' and teachers’ activities during the teaching-learning process and achievement tests to measure the students’ speaking skills. The form of the test is pretest. The results of the study showed that a series of picture activities can improve the students’ speaking skills of class Second grade of MTS Ma’arif Keputran in the academic year 2015/2016. It was shown by the students’ improvement in one cycle. The speaking skill achievement in the observation was categorized as sufficient, fair .in the first cycle, and good. The students' average scores of speaking skills were in pre-test:10,25% in the post-test (The cycle 1); 58,97%. And the research is a success.